Becoming a Platform in Europe On the Governance of the Collaborative Economy - Teli, Maurizio; Bassetti, Chiara (NowOpen, 2021)
Emerging out of the collaborative work conducted within the Working Group "Mechanisms to activate and support the collaborative economy" of the COST Action "From Sharing to Caring: Examining Socio-Technical Aspects of the Collaborative Economy", the book questions the varied set of organizational forms collected under the label of "collaborative" or "sharing" economy -ranging from grassroots peer-to-peer solidarity initiatives to corporate owned platforms- from the perspective of what is known as the European social values: respect for human dignity and human rights (including those of minorities), freedom, democracy, equality, and the rule of law. Therefore, the edited collection focuses on the governance of such economic activities, and how they organize labour, cooperation and social life. From individual motivations to participating, to platform use by local groups, until platform design in its political as well as technological dimensions, the book provides a comparative overview and critical discussion on the processes, narratives and organizational models at play in the collaborative economy. On such a basis, the volume offers tools, suggestions and visions for the future that may inform the designing of policies, technologies, and business models in Europe.